12=3(6t+1)

Simple and best practice solution for 12=3(6t+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12=3(6t+1) equation:


Simplifying
12 = 3(6t + 1)

Reorder the terms:
12 = 3(1 + 6t)
12 = (1 * 3 + 6t * 3)
12 = (3 + 18t)

Solving
12 = 3 + 18t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-18t' to each side of the equation.
12 + -18t = 3 + 18t + -18t

Combine like terms: 18t + -18t = 0
12 + -18t = 3 + 0
12 + -18t = 3

Add '-12' to each side of the equation.
12 + -12 + -18t = 3 + -12

Combine like terms: 12 + -12 = 0
0 + -18t = 3 + -12
-18t = 3 + -12

Combine like terms: 3 + -12 = -9
-18t = -9

Divide each side by '-18'.
t = 0.5

Simplifying
t = 0.5

See similar equations:

| -2.8=-0.56(m+8) | | 7(4y-5)+3(5y+4)= | | 3m-17=52 | | 3(6x+24)=18x+72 | | 2q(q-6)=0 | | 2=2v-2 | | 6(1-4y)-5y=-8(3+4y) | | 6x+9y=2 | | 2k-4=12 | | 4-3x=-3+4x | | 3.5x+1.25= | | -25k=-150 | | 82=-65-x | | -(7x+6)=-3(1+2x) | | 4m^2-12a=-8 | | 7b+3-4b=3-3(-b+4) | | 7x+9-3x=25 | | 71=23-4x | | -4x+4-2x=-s(3x-3) | | 2x^2-3y^2+8x-60y-304=0 | | 3x+48=5 | | -2+10+4= | | 3(t+6)= | | -45y=-90 | | 4-6b=40 | | -457=-90 | | 4x-10=7x-16 | | 2(150-0.5y)+y=300 | | -14=-7v | | 6a-9=3a+6 | | 80-(4x+15)=4(x+5)+x | | (2x-4)+9i=8+3i |

Equations solver categories